Low dose amitriptyline for treatment of persistent arm pain due to repetitive use - Goldman, Rose H. (2010)
Amitriptyline is sometimes used to treat arm pain related to repetitive use, but rigorous evidence of its benefit is lacking. This randomized controlled trial investigated whether amitriptyline provided greater pain relief or improved arm function than a placebo pill in adults with arm pain associated with repetitive use that had persisted for at least three months. Participants (N=118) were randomly assigned to receive 25 mg of amitriptyline or a placebo pill for 6 weeks. The primary outcome was intensity of pain (10-point numerical rating scale) and secondary outcomes were arm symptoms, arm function, grip strength, mood and sleep. Assessments were done at baseline, 3 and 6 weeks of treatment, and one month after treatment ended. Changes in arm pain were not statistically significant. However, the amitriptyline group improved more than the placebo group in arm function (p=0.023) and sense of well-being (p=0.034). In a longitudinal analysis, the amitriptyline group’s arm function score improved 0.45 points per week faster than placebo after adjusting for subject characteristics (p=0.015). At the treatment’s midpoint, the amitriptyline group reported more “troublesome side-effects” than the placebo group (52.5% vs. 27.1%, p=0.005), but this difference decreased by end of treatment (30.5% vs 22.0%, p=0.30). The most frequent side effect was drowsiness. In conclusion, this study found that low-dose amitriptyline did not significantly decrease arm pain among these participants but did significantly improve arm function and well-being. Future research is needed to explore the effects of higher doses and longer duration of treatment.